High-Frequency Trading Activities and Brokerage Firms Effect : Empirical Evidence From the Indonesia Stock Exchange - Barsiano, Redik; Hanafi, Mamduh Mahmadah; Arief, Usman (The Indonesian Capital Market Review, 2019)
This research studies the trading activity of type of traders through their brokers. Order imbalance is believed to be a better proxy for explaining trading activity. This paper presents some empirical test that on brokerage level analysis exhibit information paradigm in Indonesia which market makers and specialist are not available. We divide imbalances into groups of samples (all stocks and most liquid stocks), trader type (foreign or domestic) and size of brokerage firm (small to big). Our results show that order imbalances generally have a positive serial correlation for all the traders and brokers analyzed. However, we find that the determinant of order imbalances is a particular phenomenon at the brokerage level, whose results differ from our market-wide analysis. We do not find that previous order imbalances can predict market returns across trader type and brokerage class. In contrast, for the inventory paradigm, the evidence from the brokerage level analysis indicates that information dissemination is induced order imbalance by brokerage house.